2010
DOI: 10.1080/08111146.2010.496715
|View full text |Cite
|
Sign up to set email alerts
|

Goodbye to the Backyard?—The Minimisation of Private Open Space in the Australian Outer-Suburban Estate

Abstract: Although a substantial backyard might be considered an iconic Australian feature, by the late 1990s, almost all new suburban houses had minimal provision of soft-landscaped private open space. This paper presents results of research that has investigated important aspects of this phenomenon. It has measured the changes on a sample basis and has attempted to relate the changes to their planning policy context. The environmental significance has been assessed in relation to the literature. Quantitative analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…For instance, residentially stable neighborhoods have greenspace abundance yet greenspace inaccessibility. Residentially stable neighborhoods may reflect older planning standards that emphasized a few large greenspaces rather than an interspersion of many small greenspaces closer to homes (Hall 2010). Similarly, while concentrated affluence explains amenity poor and transport greenspace accessibility, it also explains amenity poor and transport greenspace scarcity so perhaps these findings suggest that these types are interspersed throughout affluent neighborhoods.…”
Section: [Insert Table 5]mentioning
confidence: 78%
See 1 more Smart Citation
“…For instance, residentially stable neighborhoods have greenspace abundance yet greenspace inaccessibility. Residentially stable neighborhoods may reflect older planning standards that emphasized a few large greenspaces rather than an interspersion of many small greenspaces closer to homes (Hall 2010). Similarly, while concentrated affluence explains amenity poor and transport greenspace accessibility, it also explains amenity poor and transport greenspace scarcity so perhaps these findings suggest that these types are interspersed throughout affluent neighborhoods.…”
Section: [Insert Table 5]mentioning
confidence: 78%
“…Greenspace interspersion may have important theoretical implications if neighborhoods are observed that have high greenspace accessibility but unvisited greenspace since they are too small in size to provide beneficial open-space (Urlich 1991), vegetation (Kaplan & Kaplan 1989), connectivity (Brantingham & Brantingham 1993, or amenities (Henriksen & Tjora 2014;Jacobs 1964). Alternatively, interspersion could reflect different periods of planning codes since it was also associated with residential stability (see Hall 2010). Third, my greenspace typology accuracy is highly dependent on the data quality of multiple secondary amenity data sources.…”
Section: Discussionmentioning
confidence: 99%
“…However, newer suburban developments tend to have larger houses and smaller backyards than in older communities, which may affect how the backyard is utilized and managed (Hall 2010). Patterns in vegetation and management practices at the household-scale have diverse, often taxon-specific, consequences for the abundance and diversity of invertebrate species that utilize yards as habitat or resources (Livingston et al 2003;Raupp et al 2010).…”
Section: Attitudinal and Structural Factorsmentioning
confidence: 98%
“…Methods as surveys, observations dimensions as cluster or factor analysis are preferred in the second tradition. It is not even though there are morphological analyses which use descriptive statistics for example for parameters of lots and building footprints (Hall, 2008;2010) or street patterns parameters (Southworth and Owens, 1993;Southworth and Ben-Joseph, 1997). The following two subsections describe the typo-morphological and statistical method used in the Karlstad's study.…”
Section: Methodsmentioning
confidence: 99%